An Efficient Solution To Task Scheduling And Memory Partitioning For Uniprocessor (International Journal of Engineering and Computer Science, 2015)
— A real time operating system (RTOS) is a specified time constraint in the real time application. A process ofRTOS using Open Mp, multiple tasks are concurrently running on the system. A large number of embedded applicationsrequired multiple concurrent real-time tasks. In a concurrent real-time tasks, the task scheduling and memory allocationare done on Uni-processor. These two functions are performed separately; tasks are scheduled first and then partitionedamong the processors. So, it requires an additional memory and also the waste of time period for every task. Instead ofcache memory, using SPM (Scratch Pad Memory) the execution time of embedded applications will be accuratelyprefixed. (RR) Round Robin Scheduling is used to complete a task. Every task had a scratch pad number for theallocation. Depending upon the Round Robin scheduling and Scratch pad number the task should be completed within agiven time period